Proceedings of the International Conference on Trends of Technologies and Innovations in Economic and Social Studies 2017 2017
DOI: 10.2991/ttiess-17.2017.114
|View full text |Cite
|
Sign up to set email alerts
|

Human resource risk management in organization: methodological aspect

Abstract: Abstract-The complexity, dynamism and uncertainty of the socioeconomic status of both Russian and global economies generally form a significant number of risks that threaten the effective functioning and development of organizations. Moreover, the urgency of these problems is increasing in the conditions of economic stabilization and the outlook for development, when the degree of certainty and predictability of external factors is increasing, as well as the relative influence of internal organizational factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As managers and entrepreneurs are responsible for personnel risk management, they cover three major areas: staffing, staff utilization, and staff development (Fedotova et al, 2018). On the other hand, personnel risk is a very wide term starting from framing the human resources management strategy, followed by continuous management of all internal and external sources from where the risk can possibly arise (Mitrofanova et al, 2017). Therefore, as a risk manager entrepreneur at SME must know how to identify, manage, and control it.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As managers and entrepreneurs are responsible for personnel risk management, they cover three major areas: staffing, staff utilization, and staff development (Fedotova et al, 2018). On the other hand, personnel risk is a very wide term starting from framing the human resources management strategy, followed by continuous management of all internal and external sources from where the risk can possibly arise (Mitrofanova et al, 2017). Therefore, as a risk manager entrepreneur at SME must know how to identify, manage, and control it.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In their study, provide a report from the viewpoints of different people on the types of human resource risks in three classes of human capital, structural capital, and relational capital. The following table shows these viewpoints (Mitrofanova et al, 2017). In a study of employee absenteeism risk, Mousavi, Nordin, Othman & Sulaiman (2011) identified the risk of unexpected absenteeism as a risk that companies and organizations face, and there is no way to accurately predict risk or avoid it completely.…”
Section: Resultsmentioning
confidence: 99%
“…Human resource operational issues are also a major issue for managers in other sectors. These managers state that if they do not perform these operations (related to human resources) properly, their business strategy will fail if they do not do it properly (human resources) (Mitrofanova et al, 2017)". Given the importance of the subject of this article, the aim of this study is to analyze the human resource risk management framework and the factors influencing it.…”
Section: Introductionmentioning
confidence: 99%
“…What can be observed in the literature on risk management is the appearance of a new trend in theoretical and business research, namely human resource risk management (cf. Oborilová et al, 2015;Huang et al, 2017;Mitrofanova et al, 2017). The causes for the appearance of risk in human resource management can be seen in, for example, insufficient qualifications of employees and management teams, inadequate decisions made during the recruitment process, a poorly functioning system of employee training and development, shortcomings of the remuneration and incentive system, non-compliance with ethical principles, and failure of employees to comply with legal regulations, as well as other rules and procedures functioning in the enterprise (Bochniarz and Gugała, 2005;Lipka, 2002).…”
Section: The Role Of Risk Management In Human Resource Managementmentioning
confidence: 99%